2015
DOI: 10.1039/c5ra02882e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and photocurrent generation of a new nanocomposite based Cu–TCPP MOF and ZnO nanorod

Abstract: Schematic representation of the Cu–TCPP MOF/ZnO (15%) nanocomposite on an FTO substrate in the photoelectrochemical cell and the mechanism of the photocurrent generation (the chemical potentials were calculated by cyclic voltammetry measurement).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…The cycle is continued by the reduction of O 2 at the interface and by transfer of electrons from the reduced O 2 ( normalO2) to the porphyrin cation in TGP. Therefore, the ground state of porphyrin is recovered .…”
Section: Resultsmentioning
confidence: 99%
“…The cycle is continued by the reduction of O 2 at the interface and by transfer of electrons from the reduced O 2 ( normalO2) to the porphyrin cation in TGP. Therefore, the ground state of porphyrin is recovered .…”
Section: Resultsmentioning
confidence: 99%
“…Compared to conventional light-harvesting organic polymers, MOFs possess long-range order and are comprised of metal ions or clusters that are connected by electron-donating ''linker'' groups to create a networked structure with well-defined pores. [26][27][28] In conclusion, we have synthesized a photoconductive Cd(II)-MOF which has two band gaps as demonstrated both from experimental measurements and DFT calculations. The synthesized complex exhibits strong absorbance in the wavelength range of 345-390 nm, which predicts some impact of incident radiation on the charge transport phenomena.…”
mentioning
confidence: 80%
“…According to our finding about porphyrin based MOF in the previous work and as can be seen in the DRS spectra of TGSP, it is found that the highly efficient light-harvesting structure of the SnTCPP pillared TG composite can be attributed to densely embedded porphyrin chromophores with high visible absorptivity within the framework [23]. The excited electrons of SnTCPP transfer from SnTCPP to TiO 2 through the bond between the tin atom and the hydroxyl group of TiO 2 surface.…”
Section: Description Of Photocatalytic Activitymentioning
confidence: 92%